New forms of work organisation 2 : German Democratic Republic, India, Italy, USSR, Economic costs and benefits - International Labour Office (Geneva : International Labour Office, 1979)
This second volume of a series devoted by the International Labour Office to the subject of a new forms of work organization. Thus in addition to a first volume containing monographs concerning Denmark, Norway and Sweden, France, Federal Republic of Germany, United Kingdom and the United States, the Office is also publishing national monographs concerning the German Democratic Republic, India, Italy, and the USSR, together with a paper on achievements and possibilities with regard to the evaluation of the economic costs and benefits of new form of work organization.
Includes bibliographical references: p. 142-145.
rpm 05/12/2017
Loans
Keywords: Working class; Industrial organization; Work design